2012
DOI: 10.1038/ncomms2228
|View full text |Cite
|
Sign up to set email alerts
|

Supercooled liquids with enhanced orientational order

Abstract: The nature of the glass transition, the transformation of a liquid into a disordered solid, still remains one of the most intriguing unsolved problems in materials science. Recent models rationalize crucial features of vitrification with the presence of medium-range ordered regions coexisting with the isotropic liquid. Here, in line with this prediction, we report an extraordinary enhancement in bond orientational order in ultrathin films of supercooled polyols, grown by physical vapour deposition. By varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 41 publications
7
47
0
Order By: Relevance
“…45,46 Capponi et al reported an analogous feature observed by dielectric spectroscopy. 47 On the other hand, a recent SIMS study 26 suggested that the self-diffusion coefficient D of the liquid transformed from ultrastable IMC glass does not differ from the value of D of the conventional supercooled counterpart. Based on a first order liquid-liquid transition derived from theoretical considerations by Matyushov and Angell, 48 the ultrastable glass to liquid transitions have been viewed as indicators of the existence of thermodynamically different liquid states, at least for fragile systems.…”
Section: Resultsmentioning
confidence: 99%
“…45,46 Capponi et al reported an analogous feature observed by dielectric spectroscopy. 47 On the other hand, a recent SIMS study 26 suggested that the self-diffusion coefficient D of the liquid transformed from ultrastable IMC glass does not differ from the value of D of the conventional supercooled counterpart. Based on a first order liquid-liquid transition derived from theoretical considerations by Matyushov and Angell, 48 the ultrastable glass to liquid transitions have been viewed as indicators of the existence of thermodynamically different liquid states, at least for fragile systems.…”
Section: Resultsmentioning
confidence: 99%
“…Parallel to the study of the interfacial layer in polymer nanocomposites, various studies of polymers adsorbed thermally or/and chemically on solid surfaces [19,20,22,23], as well as of thin polymer films [24], have demonstrated similarities between polymer nanocomposites and thin polymer films in thermal stability, polymer chain conformations and dynamics. Core-shell based nanocomposites [25,26] form a next class of interest in the same direction, where the polymer is adsorbed in multiple layers (shells) onto the nanoparticles (core).…”
Section: Introductionmentioning
confidence: 99%
“…A linear growth of the mean-squared displacement (MSD) with increasing temperature is predicted by the Nyquist (fluctuation-dissipation) theorem [1,2]. The MSD is experimentally extracted from either the intermediate scattering function of the neutron scattering experiment [3] or from the fraction of recoilless γ-ray emission of the 57 Fe nucleus in the Mössbauer experiment [4,5]. The Nyquist theorem was found to be violated for a number of glassforming materials, where a kink in the MSD vs. temperature is often observed at the laboratory glass transition [6].…”
Section: Introductionmentioning
confidence: 99%